Configuraciones organizacionales del modelo de Bert Hellinger y su influencia en la gestión del talento humano (2020)
This research project seeks to understand the tool proposed by the Psychologist Bert Hellinger as an organizational system from a family point of view to a business point of view. Each author is implementing, adding theory to a tool that evolves over the years, for this reason, we can unite these concepts, analyze them and reach conclusions, which will be beneficial for companies seeking to implement this idea. Therefore, this project is carried out with the compilation of information from various authors who implemented or contributed ideas for this tool for organizational constellations.